Three-dimensional smoothed particle hydrodynamics modeling of near-shore current flows over rough topographic surface - Gabreil, Eslam; Wu, Haitao; Chen, Chen; Li, Jiaye; Rubinato, Matteo; Zheng, Xing; Shao, Songdong (Frontiers in Marine Science, 2022)
In this study, a three-dimensional (3D) numerical model based on the smoothed particle hydrodynamics (SPH) approach was developed to simulate the near-shore current flows over a rough topographic surface in the coastal area, where the flows are shallow and demonstrate strong turbulent characteristics. The numerical program is based on the open-source code SPHysics (http://www.sphysics.org), and two major improvements are made to treat the turbulence and rough boundary effects: A modified sub-particle-scale (SPS) eddy viscosity model is developed to address the turbulence transfer of flows, and a drag force equation is included in the momentum equations to account for the influence of roughness element on the bed and lateral boundaries. The computed results of flow velocity, shear stress, and free surface characteristics are compared with the laboratory measurements for a variety of test conditions. It has shown that the present SPH model can accurately simulate 3D-free surface near-shore current flows over a realistic topography with roughness.